Impact of Teenage Relationship to the Academic Performance of Grade 12 ABM Students in Bestlink College of the Philippines S.Y. 2018-2019 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
In this study, it shows the impact of teenage relationship to the academic performance of Grade 12 ABM students in Bestlink College of the Philippines. Some of the students nowadays, especially in Senior High School, experience this kind of problem. The purpose of this research is to determine the impact of teenage relationship to the academic performance of Grade 12 Accountancy, Business and management students of Senior High School at Bestlink College of the Philippines. Specifically, it sought to answer the following reasons for teenagers getting into a relationship in terms of the following variables: Family Orientation, Lack of Guidance, Peer Influence, and Curiosity. The researchers used a descriptive research design and purposive sampling technique. There were five (5) students selected from each of the ten (10) sections for a total of fifty (50) respondents from Accountancy, Business and Management Strand. This study will help elaborate on the impact of teenage relationships in the academic performance of many young students involved in this kind of relationship. The result of the study shows the impact of teenage relationships on academic performance in Grade 12 ABM students is MOTIVATED with an average mean of 3.68. This means students who were engaged in a teenage relationship feel motivated and inspired while studying. The study determined that there were positive effects of teenage relationships on students who were engaged in them as reflected in their good standing in their academic performances. Therefore, the cited variables in the study are all agreed upon by the respondents.
Keywords: feelings, impact, relationship, experience,teenage, motivation, inspiration